INTERPRETATION OF ISSUES REGARDING THE ROLE AND CHARACTERISTICS OF ARTISTIC LITERATURE IN MASTERING RUSSIAN LANGUAGE LESSONS IN HIGHER EDUCATION - Sardor Himmatov Sardor o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2024)
The article discusses the importance of literature in mastering the Russian language, in particular, it is noted that literature always plays an important role, because it is created to form the appropriate level of the ability to read and understand what is read. Also, studies are given on how literary science can help to familiarize people with cultural values and expand the range of cultural and educational interests.